An Economic Model for the Division of Labor - Kilbridge, Maurice; Wester, Leon (Management Science, 1966)
The division of labor in assembly is facilitated by the conveyor line. Workers are stationed along the line on which the frame of the product being assembled moves. The total job is broken into elements of work and assigned in approximately equal shares to the workers on the line. Each operator adds his share of work as the product passes him. The measure of the division of labor is the amount of time the product spends at each operator's work station. This period is commonly called the “cycle time.” The problem of the economic extent of the division of labor is to determine the optimum cycle time, or that which yields the lowest unit direct labor cost of assembly.